2018
DOI: 10.4236/msce.2018.64005
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Preparation of Catalysts for Carbonyl Sulfide Hydrolysis under Moderate Temperature

Abstract: Multifunctional composite catalyst for carbonyl sulfide hydrolysis under moderate temperature was prepared by impregnation method. The hydrolysis and deoxidization ability of the prepared catalyst was investigated in a fixed bed reactor. It was found that deoxidization ability of the prepared catalyst was raised by the increase of the content of potassium loading catalyst and reaction temperature. And the concentration of H 2 S had no effect on deoxidization while COS improved the deoxidization ratio. And deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Not always does the addition of other components have a positive effect on the reaction performances of the hydrolysis catalyst. Xu et al 62 reported a study on the promotion of Al 2 O 3 with Mo and K, with the aim of improving the deoxidization ability of the catalyst. In fact, the authors observed that the presence of oxygenated compounds in the reacting system may lead to sulfidation of the catalyst.…”
Section: High-temperature Cos Hydrolysismentioning
confidence: 99%
“…Not always does the addition of other components have a positive effect on the reaction performances of the hydrolysis catalyst. Xu et al 62 reported a study on the promotion of Al 2 O 3 with Mo and K, with the aim of improving the deoxidization ability of the catalyst. In fact, the authors observed that the presence of oxygenated compounds in the reacting system may lead to sulfidation of the catalyst.…”
Section: High-temperature Cos Hydrolysismentioning
confidence: 99%